STRENGTH CHARACTERISTICS OF CONCRETE MADE WITH RECYCLED CONCRETE AGGREGATE (RCA), MICRO-SILICA AND POLYPROPYLENE FIBRE - ADESOLA OLAYINKA ADETUKASI; ADEOYE MOSES OLOWOFOYEKU; HAFIZ A. ALAKA; OMOWUMI ADEBAYO (Journal of Engineering Studies and Research, 2023)
Recycled concrete aggregate has been widely researched to be capable of replacing natural coarse aggregate in concrete, however, with some inadequacies in its concrete’s ability to attain the same feat in mechanical properties as normal concrete. This research work attempts to improve the strength characteristics of concrete containing recycled coarse aggregate with the addition of admixtures (Micro-Silica and Superplasticizer) and Polypropylene fibre. Results showed that admixtures significantly improved the workability and mechanical properties of CRCA at all RCA replacement levels. Addition of PPF had significant effect on the flexural and splitting tensile strengths of CRCA, but not much impact on the compressive strength.